Acute Severe Mitral Regurgitation Secondary to Papillary Muscle Rupture: A Rare Mechanical Complication of Acute Myocardial Infarction - Barakoti, Murari Prasad (Journal of National Heart and Lung Society Nepal, 2022)
Acute myocardial infarction in current era is detected promptly and emergent percutaneous intervention is initiated in most part of the world as a standard of care which has led to significant reduction in all the complications associated with acute myocardial ischemia. A 46-year-old man presented with acute onset of chest pain and shortness of breathand was found to have a non ST-segment elevation myocardial infarction and acute mitral regurgitation due to papillary muscle rupture. This case describes a rare and potentially fatal mechanical complication of acute myocardial infarction. Use of transesophageal echo guides for the understanding the mechanism and guide the management.